Peran Partisipasi Masyarakat dalam Mendukung Penaatan Ruang Berkelanjutan di Kota Tasikmalaya - Raisa, Azkiya; Joas Bery Steven Purba; Ardiansyah Ali; Siti Fadjarajani; Cahya Darmawan (Indonesian Journal of Glasial Geography, 2025)
This study aims to analyze the role of community participation in supporting sustainable spatial compliance in Tasikmalaya City. Using a qualitative approach, data were collected through interviews, observations, and document studies. The results indicate that community participation is still limited by a lack of understanding of spatial regulations, limited access to information, and economic pressures. However, positive participation potential arises from local communities and the younger generation in maintaining sustainable land functions. Active involvement from local government and related institutions is essential to enhance socialization, education, and strengthen inclusive and adaptive participation mechanisms. These findings highlight that synergy between the community and government is the key to realizing sustainable spatial planning in Tasikmalaya City..